A sound potential against energy dependency and climate change challenges: Floating photovoltaics on water reservoirs of Turkey. (April 2023) - Kulat, Muhammed Imran; Tosun, Kursad; Karaveli, Abdullah Bugrahan; Yucel, Ismail; Akinoglu, Bulent Gultekin
Abstract: Energy security and climate change are among the top priority challenges for Turkey. High dependency on imported resources jeopardizes the economy, especially with high currency rate and conflicts in neighboring countries from where Turkey imports its energy. Besides, Turkey has already started to experience the impacts of climate change such as increasing temperature along with drought. Floating photovoltaics have proven themselves to be quite efficient in energy production, with evaporation reduction as a positive externality. The purpose of this article is to reveal the possible capacity of floating photovoltaics on constructed water reservoirs of Turkey and draw policy perspectives against existing or anticipated challenges. A total of 4, 003 reservoirs were analyzed based on different water surface coverage scenarios. The results of the study proposed 125 TWh electricity generation, slightly above 40% of the nation-wide electricity demand, when 10% of suitable reservoirs were covered. This generation would be highly instrumental in reducing energy dependency and substituting renewables for conventional resource uses. Avoided CO2, thanks to this substitution, was calculated to be 77.1 Mton equivalent. This would obviously be favorable in light of the carbon emission reduction policy of the country and Paris Agreement requirements. Moreover, 1, 242.1 hm 3 freshwater was assessed to save resources from evaporation loss, which would help to mitigate the climate change pressure on water resources. Highlights: Turkey is 74% dependent to import energy resources. A model proposing suitable reservoirs for floating photovoltaic is presented. 125 TWh electricity can be generated if 10% of the reservoir surfaces are covered. Water saving is 1, 242 hm 3 : enough to supply 15 M people or hydroelectric as $32.3 M. 77.6 million tons CO2 equivalent is avoided.